Raman microspectroscopic analysis of bioactive in palm oil-in-water emulsions stabilised by dairy protein - Wan Anwar Fahmi Wan Mohamad
The quest for designing a stable encapsulation system for natural bioactive in food products has never stopped. The development and innovation of analytical instruments allows for new factors influencing the system design to be explored. It is believed that the partitioning of bioactive within an emulsion affects the stability of the system, and so understanding it may inform the development of stable formulations as carriers for health promoting bioactives. This research is focussed on analysing the partitioning characteristics of a bioactive carried in emulsion systems, using a powerful but as yet relatively unexplored technique in food-related studies; in-situ confocal Raman microspectroscopy (CRM). Stable food-grade palm oil-in¬water (O/W) emulsions were engineered for the encapsulation of natural arotene content of oil droplets within emulsion systems. The Raman image obtained shows that the bioactive molecules were dispersed into both the oil and aqueous phases of the emulsions, but at a much higher concentration in the former. Next, it was found that increasing the p-carotene concentration (from 0.1 to 0.3 g/kg emulsion) at a fixed gross composition of an emulsion (10% palm 0Iein:2% WPl) reduced the concentration of -carotene throughout 30 d storage at 20 and 40°C. It was found that a higher composition of J3-carotene was in the aqueous phase at the end of the storage period, suggesting that